ANALISIS TINGKAT KEUSANGAN LITERATUR PADA SKRIPSI MAHASISWA DEPARTEMEN FISIKA FAKULTAS MATEMATIKA DAN ILMU PENGETAHUAN ALAM UNIVERSITAS NEGERI PADANG TAHUN 2021 - Prima Pracelia (ADISAM PUBLISHER, 2023)
This study aims to (1) describe the half-life of the literature used in the 2021 Student Thesis of the Department of Physics, Faculty of Mathematics and Natural Sciences, (2) to describe the level of obsolescence of literature that occurs in Student Thesis of the Department of Physics, Faculty of Mathematics and Natural Sciences, 2021. This research uses a type of quantitative research using descriptive methods through documentation by directly analyzing the bibliography of the thesis. The population of this research is the student thesis of the Department of Physics, Faculty of Mathematics and Science, Padang State University in 2021 with 74 thesis titles. The results of this study indicate several things as follows. First, the characteristics of the literature in the student thesis of the Department of Physics, FMIPA UNP, includes the type and age of literature. The most cited types of literature were books and journals with 1372 and 1232 citations. Second, the half life age in the student thesis of the Department of Physics FMIPA UNP is at the age of 6, therefore the obsolescence rate is 1276 citations and then the remaining 9013 are considered obsolete